Macroalgae Diet Indicates Potential in Mariculture Production of Shoemaker Spinefoot Rabbitfish - Athman Bacha, Najda; Munga, Cosmas; Mirera, David (Multidisciplinary Journal of Technical University of Mombasa, 2024)
Worldwide, fish feed is known to be costly in aquaculture production majorly contributed by the cost of fish meal which is widely used as a protein ingredient in fish diet causing a great problem for the development and growth of the aquaculture sector. Therefore, seeking other sources that will be satisfactory, such as alternative protein for fish feed and providing nutritional benefits at a lower price is very important. This study aimed to explore the nutritional profile of the most preferred naturally occurring marine macroalgae species commonly utilized as bait for the basket trap fishery targeting rabbitfish. Data was collected through random administration of questionnaires to 62 fishers from Mkunguni, Kibuyuni, and Kijiweni fish landing sites in South Coast Kenya. A total of 6 species of rabbitfish were identified as targets for basket trap fishers. These were: Siganus stellatus, Siganus sutor, Siganus luridus, Siganus canaliculatus, Siganus argenteus and Siganus rivulatus. Results showed that fishers mostly preferred three species of marine macroalgae as bait for Rabbitfish including Chondrophycus papillosus, Fischerella sp, and Chaetomorphus crassa. The most preferred marine macroalgae were taken to the laboratory for proximate composition analysis. In terms of nutritional profile, all species were rich in carbohydrates > 21.60 ± 0.07 (g/100g) and energy > 245.65 ± 0.58 (g/100g) levels. Total fat content was the least 0.48 ± 0.01 (g/100g) whereas no significant difference > 0.05 was observed in moisture content. Fischerella sp accounted for the highest protein content levels 33.88 ± 0.02 (g/100g) compared to other species.